Effect of Polyvinyl Alcohol on Cassava and Potato Starch Plastic Film: Mechanical, Thermal and Swelling Properties - Adnan, Nor Atika; Meriam Suhaimy, Syazwan Hanani (Enhanced Knowledge in Sciences and Technology, 2023)
Uncontrolled use of synthetic plastic has triggered environmental concern due to the decomposition issue that are still not highly efficient and relatively lead to the production of high plastic waste. Due to these circumstances, biodegradable plastic film from natural polymers like cassava and potato starch is developed. However, the brittleness and low mechanical strength of starch based plastic film has contributed to the development of polymer blending between starch and polyvinyl alcohol (PVA) to produce starch/PVA bioplastic film. By using casting method, different proportion of 4% PVA (30% and 60% based on starch weight (dry basis)) solution was added into the starch film-forming solution and the effect of PVA content to cassava and potato starch bioplastic films was studied. After several analysis, it was found that the increment of PVA reduce the thickness of both cassava and potato starch bioplastic films, while at the same time increase the moisture content, swelling capacity and biodegradation rate of this biodegradable films. In addition, bioplastic films from cassava starch shows the higher swelling capacity and biodegradation rate than potato starch plastic film due to its increment in hydrophilicity after blending with PVA. It is also shown that the tensile stress for cassava plastic film increases significantly (p